In vitro characterization of MG‐63 osteoblast‐like cells cultured on organic‐inorganic lyophilized gelatin sponges for early bone healing. Issue 8 (19th April 2016) - Rodriguez, Isaac A.; Saxena, Gunjan; Hixon, Katherine R.; Sell, Scott A.; Bowlin, Gary L.
Abstract: The development of three‐dimensional porous scaffolds with enhanced osteogenic and angiogenic potential would be beneficial for inducing early‐stage bone regeneration. Previous studies have demonstrated the advantages of mineralized and nonmineralized acellular 1‐Ethyl‐3‐[3‐dimethylaminopropyl]carbodiimide hydrochloride (EDC) cross‐linked gelatin sponges enhanced with preparations rich in growth factors, hydroxyapatite, and chitin whiskers. In this study, those same scaffolds were mineralized and dynamically seeded with MG‐63 cells. Cell proliferation, protein/cytokine secretion, and compressive mechanical properties of scaffolds were evaluated. It was found that mineralization and the addition of growth factors increased cell proliferation compared to gelatin controls. Cells on all scaffolds responded in an appropriate bone regenerative fashion as shown through osteocalcin secretion and little to no secretion of bone resorbing markers. However, compressive mechanical properties of cellularized scaffolds were not significantly different from acellular scaffolds. The combined results of increased cellular attachment, infiltration, and bone regenerative protein/cytokine secretion on scaffolds support the need for the addition of a bone‐like mineral surface. Cellularized scaffolds containing growth factors reported similar advantages and mechanical values in the range of native tissues present in the early stages of bone healing. These results suggest that the developed composite sponges exhibited cellular responses and mechanical properties appropriate for promoting early bone healing in various applications. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 2011–2019, 2016.